Development of a Web-Based Stress Screening and Counseling Referral System for Early Intervention - Shofwatun Amaliyah; Dody Indra Sumantiawan; Puspita Puji Rahayu; Barans Irawan Palangan (ILMU PSIKOLOGI, 2026)
Student mental health has become an increasingly important issue in higher education due to the rising prevalence of stress and psychological distress among university students. Limited accessibility to mental health services and the lack of integration between early detection and intervention systems often hinder timely psychological support. This study aimed to develop and evaluate an integrated web-based stress screening and counseling referral system as an early mental health intervention model for university students. The study employed a research and development approach involving needs analysis, system development, instrument validation, pilot testing, implementation, and evaluation. A total of 180 university students participated in the study. Data were collected using a web-based stress screening instrument integrated with an automated scoring and adaptive referral mechanism. The findings revealed that most participants were categorized within moderate to high stress levels, indicating the urgent need for preventive mental health services in higher education settings. The developed system demonstrated effective identification of stress levels and facilitated students’ engagement with recommended counseling services. These results suggest that the integrated system provides a scalable and technology-driven framework for improving early mental health intervention and promoting help-seeking behavior among university students.